Everybody needs a rock - Baylor, Byrd.; Parnall, Peter (New York : Aladdin Paperbacks, 1985)
Describes the qualities to consider in selecting the perfect rock for play and pleasure.
"Aladdin picture books"--Cover.
Book Links (A.L.A.).
Library Journal.
School Library Journal.
3.4.
3.4
Keywords: Rocks -- Fiction; Rocks -- Fiction